2011
DOI: 10.1159/000335417
|View full text |Cite
|
Sign up to set email alerts
|

ADAM33 as a Psoriasis Susceptibility Gene in the Han Population of Northeastern China

Abstract: Background: A disintegrin and metalloprotease 33 (ADAM33) has recently been suspected to be associated with psoriasis. Objective:To study the association between ADAM33 and psoriasis in the northeastern Chinese Han population. Methods: We genotyped six common single nucleotide polymorphisms from ADAM33 in 400 psoriasis cases and 398 controls using the Multiplex SNaPSHOT method. Results: We observed an increased risk of psoriasis to be associated with the rs2787094CC CG, rs528557CC CG genotypes (p < 0.05) and 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Some gene polymorphisms have been shown to be associated with psoriasis. In our previous study, we found that a gene for disintegrin and metalloprotease‐33 is a psoriasis susceptibility gene in the Han population of northeastern China, and we also reported a new susceptibility locus for psoriasis within the late cornified envelope (LCE) gene cluster . However, how many additional gene polymorphisms are also involved in individual susceptibility to psoriasis remains unknown.…”
Section: Introductionmentioning
confidence: 98%
“…Some gene polymorphisms have been shown to be associated with psoriasis. In our previous study, we found that a gene for disintegrin and metalloprotease‐33 is a psoriasis susceptibility gene in the Han population of northeastern China, and we also reported a new susceptibility locus for psoriasis within the late cornified envelope (LCE) gene cluster . However, how many additional gene polymorphisms are also involved in individual susceptibility to psoriasis remains unknown.…”
Section: Introductionmentioning
confidence: 98%
“…CARD8 may be involved in psoriasis development as a genetic marker or a causative polymorphism. Previously, our team identified a relationship between several other genetic polymorphisms and PsV [14,[27][28][29]. We will compile these findings to further explore the relationship between these genes and PsV in the Han population of northeastern China.…”
Section: Resultsmentioning
confidence: 93%
“…MMP-1 [160], MMP-2 [45,157,160], MMP-3 [25], MMP-7 [109], MMP-8 [38], MMP-9 [5,14,45,157,160], MMP-12 [160,167], MMP-14 [45], MMP-15 [45], MMP-19 [166], MMP-26 [167], MMP-28 [196], ADAM-10 [109], ADAM-12 [109], ADAM-17 [75], ADAM-33 [3,198] • Adalimumab/Infliximab (anti-TNF-α Ab)…”
Section: Psoriasismentioning
confidence: 99%